Linking sports registration information and player feedback to enhance netball participation - Bridget C. Foley; Catriona Rose; Katherine B. Owen; Lindsey J. Reece (BMC, 2021)
Abstract Background Sports should endeavour to provide inclusive opportunities for all people to participate. More evidence is required to understand who joins sports clubs and what keeps participants engaged throughout their lifetime. Little is known about who plays netball or what drives participation and retention of players in netball. This study aimed to identify the sociodemographic characteristics of Netball New South Wales (NSW) members, their odds of re-registering in the sport, and explore their motivations to play, experiences during participation and the perceived benefits of playing netball. Methods We used longitudinal sport registration data from all Netball NSW members in 2018 and 2019. A cross-sectional online survey was sent to all players registered during the two-year study period (n = 157,152). We used logistic regression to determine the odds of individuals returning to netball in 2019 after playing in 2018 and linked the sports registration data with the survey responses, calculating frequencies and proportions. Results Netball NSW members were mostly female (98 %) and aged less than 18 years old (69 %). Netball NSW retained 68 % of members in 2019 who played the previous year. Members who were male, aged 18-44 years old, lived in low SES areas, lived in regional/remote locations, identified as Aboriginal or Torres Strait Islander, spoke a language other than English at home or were born outside Australia had lower odds of returning to play from 2018 to 2019. Survey participants (n = 10,795) rated their experience playing netball highly and reported that playing netball improved their health and wellbeing. The main reason to play netball reported was 'fun and enjoyment' while the main reason to consider quitting was the 'skill/experience of umpires and officials'. Conclusions This study highlights the strengths of netball in engaging and retaining females, who often participate in less sport than males. The positive experiences reported by netball participants should be fostered to retain current participants throughout the lifecourse. The data provided by members should be inform strategic actions to enhance netball participation for sociodemographic groups who had greatest odds of dropout. Routine surveillance using linked registration and player feedback should be utilised by sports to enhance sport delivery and increase participation.